Gender Preference in Doctor Selection on Telemedicine: Patient Trust and Comfort Analysis - Muhammad Rio Fariza; Tita Melia Milyane; Muhammad Al Assad Rohimakumullah (Ianna Journal of Interdisciplinary Studies)
Background: Telemedicine lets people choose physicians according to several criteria, including gender. Few studies, however, investigate how doctor gender affects patient comfort, trust, and preferences.